Solve for \(m\,\): \(3mn^2 - p = q\)

\(m = \dfrac{q + p}{3n^2}\)

Solve for \(a\,\): \(ma + R = na - pa + Q\)

\(a = \dfrac{Q - R}{m - n + p}\)

Solve for \(L\,\): \(P = 2W + 2L\)

\(L = \dfrac{P}{2} - W\)

Solve for \(q\,\): \(\dfrac{1}{f} = \dfrac{1}{p} + \dfrac{1}{q}\)

\(q = \dfrac{fp}{p - f}\)

Solve for \(r\,\): \(I = Prt\)

\(r = \dfrac{I}{Pt}\)

Solve for \(x\,\): \(xy - b = t\)

\(x = \dfrac{t + b}{y}\)

Solve for \(x\,\): \(\dfrac{x}{t} + m = b\)

\(x = t(b - m)\)

Solve for \(x\,\): \(\dfrac{4x - t}{y} = y\)

\(x = \dfrac{y^2 + t}{4}\)

Solve for \(x\,\): \(\dfrac{y + t}{x} = m\)

\(x = \dfrac{y + t}{m}\)

Solve for \(x\,\): \(xt + x = m\)

\(x = \dfrac{m}{t + 1}\)

Solve for \(x\,\): \(\dfrac{xm + b}{3} = xt\)

\(x = \dfrac{b}{3t - m}\)

Solve for \(x\,\): \(u = xk + y\)

\(x = \dfrac{u - y}{k}\)

Solve for \(a\,\): \(am = np + x\)

\(a = \dfrac{np + x}{m}\)

Solve for \(a\,\): \(g = -3a + 6 + 2b\)

\(a = \dfrac{2b - g + 6}{3}\)

Solve for \(x\,\): \(z = \dfrac{4 + 3x}{4y}\)

\(x = \dfrac{4yz - 4}{3}\)